Antifibrotic Mechanism of Piceatannol in Bleomycin-Induced Pulmonary Fibrosis in Mice - Sheng, Hanjing; Lin, Gang; Zhao, Shengxian; Li, Weibin; Zhang, Zhaolin; Zhang, Weidong; Yun, Li; Yan, Xiaoyang; Hu, Hongyu (Frontiers in Pharmacology, 2022)
Background: Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal interstitial lung disease characterized by myofibroblasts accumulation and extracellular matrix deposition, which lead to irreversible damage of the lung’s architecture and the formation of fibrotic lesions. IPF is also a sequela in serious patients with the Coronavirus Disease 2019 (COVID-19). The molecular mechanisms under pulmonary fibrosis remains unclear and there is no satisfactory treatment currently. Piceatannol (PIC), is a naturally occurring resveratrol analogue found in a variety of dietary sources such as grapes, passion fruit, and white tea. It has been reported to inhibit Liver fibroblasts growth and exhibited various anti-tumor activities. While its role in pulmonary fibrosis has not been established yet. In the present study, we evaluated the antifibrotic role of PIC in bleomycin (BLM)-induced pulmonary fibrosis in mice. Methods: Mice with BLM-induced pulmonary fibrosis were treated with PIC, and fibrotic changes were measured using Hematoxylin-eosin (H&E) staining and hydroxyproline assay. Luciferase assay, western blot assay, histology analysis and immunofluorescence staining were used to evaluated the effect of PIC on fibroblasts activation and autophagy in NIH3T3 and HFL1 cells. The antifibrotic mechanisms of PIC were either confirmed in vivo. Results: Our results showed that PIC significantly alleviated the bleomycin-induced collagen deposition and myofibroblasts accumulation. In vitro and in vivo studies indicated that PIC plays an role on activating autophagy in the process of anti-fibroblasts activation. Further mechanism studies demonstrated that PIC can promote autophagy via inhibiting TGF-β1-Smad3/ERK/P38 signaling pathway, which leads to the decreased number of activated myofibroblasts. Conclusion: our study demonstrated for the first time that PIC possesses the protective effects against bleomycin-induced pulmonary fibrosis with several mechanisms, including direct pulmonary protective effects, and enhance the effect of autophagy in vitro and in vivo, and finally leads to the decreased number of activated myofibroblasts. PIC may serve as a candidate compound for pulmonary fibrosis therapy and attenuates the sequelae of SARS-COV-2 pulmonary fibrosis.